Uptake and localization of fluorescently‐labeled Karenia brevis metabolites in non‐toxic marine microbial taxa. Issue 1 (26th November 2018) - J. Kramer, Benjamin; J. Bourdelais, Andrea; Kitchen, Sheila A.; Taylor, Alison R.
Abstract : Brevetoxin (PbTx) is a neurotoxic secondary metabolite of the dinoflagellate Karenia brevis . We used a novel, fluorescent BODIPY‐labeled conjugate of brevetoxin congener PbTx‐2 (B‐PbTx) to track absorption of the metabolite into a variety of marine microbes. The labeled toxin was taken up and brightly fluoresced in lipid‐rich regions of several marine microbes including diatoms and coccolithophores. The microzooplankton (20–200 μm) tintinnid ciliate Favella sp. and the rotifer Brachionus rotundiformis also took up B‐PbTx. Uptake and intracellular fluorescence of B‐PbTx was weak or undetectable in phytoplankton species representative of dinoflagellates, cryptophytes, and cyanobacteria over the same (4 h) time course. The cellular fate of two additional BODIPY‐conjugated K. brevis associated secondary metabolites, brevenal (B‐Bn) and brevisin (B‐Bs), were examined in all the species tested. All taxa exhibited minimal or undetectable fluorescence when exposed to the former conjugate, while most brightly fluoresced when treated with the latter. This is the first study to observe the uptake of fluorescently‐tagged brevetoxin conjugates in non‐toxic phytoplankton and zooplankton taxa, demonstrating their potential in investigating whether marine microbes can serve as a significant biological sink for algal toxins. The highly variable uptake of B‐PbTx observed among taxa suggests some may play a more significant role than others in vectoring lipophilic toxins in the marine environment.